Wide Range Mechanical Customization of Mg-Gd Alloys With Low Degradation Rates by Extrusion - Harmuth, Jochen; Wiese, Björn; Bohlen, Jan; Ebel, Thomas; Willumeit-Römer, Regine (Frontiers in Materials, 2019)
Currently, only a few magnesium alloys have been approved for implant applications. For biomedi-cal purposes, the choice of the alloying elements is a critical parameter and rare earth elements have been proven to be mechanically suitable and biologically tolerable. In this comprehensive study, tailoring the mechanical properties of binary Mg-Gd alloys by indirect extrusion is shown to obtain a property profile that is applicable to different biomedical applications. Mg-2Gd, Mg-5Gd and Mg-10Gd were solid solution treated before extrusion. For each alloy various combinations of extrusion temperature and speed were applied. Resulting effects of alloy composition and processing on microstructure development, texture evolution, mechanical properties and degradation behaviour were investigated. Grain sizes and corresponding textures were adjusted by the extrusion parameters. Despite minor changes in the texture, grain boundary strengthening effects were confirmed for all alloys in accordance with the Hall-Petch relationship. The alloy composition contributed to the mechanical properties by solid solution strengthening and a combination of texture changes and slip activities. Consequently, mechanical properties can be tailored within a wide range resulting in tensile yield strengths of 90 - 200 MPa (ultimate tensile strengths 180 – 280 MPa) and compressive yield strengths of 80 - 220 MPa (ultimate compressive strengths 300 – 450 MPa) with elongations of 10 - 45%. Low degradation rates in the range of 0.2 mm/year were determined for all alloys. Degradation was only slightly influenced by the alloy composition but not affected by pro-cessing. Overall, the properties of Mg-Gd determined in this work appear to be suitable to future implant applications.